(untitled) (Journal of the College of Basic Education, 2024)
The aim of the research is to prepare an educational curriculum according to the (Merril) model and to prepare educational units according to the (Merril) model to learn the skill of handstand in artistic gymnastics and to identify the effect of educational units according to the (Merril) model in learning the skill of handstand in artistic gymnastics. The researchers used The experimental method based on. In the experimental method, where the two groups are experimental and control, the research population consists of third-year students in the Department of Physical Education and Sports Sciences, College of Basic Education, Al-Mustansiriya University for the academic year (2023-2024), numbering (93) male and female students in three halls, the first hall 31 students and the second hall. 30 students and the third hall were distributed from 32 students, which was determined intentionally. (22) female students were excluded. The researchers relied on (15) students from the third hall for the purpose of conducting exploratory experiments. As for the research sample, it was determined in a regular random manner (lottery). It was distributed The research sample consisted of two experimental and control groups. The first hall was represented by the experimental group and the second hall was represented by the control group, with (36) students for each group, representing 38.70%. The researchers followed field procedures for the research, such as a pre-test and conducting an experiment through my education according to the educational model (Merril). In addition to the post-test, one of the most important conclusions of the research is the effective and positive impact of the educational program according to the educational model (Merril), which contributed to learning handstand skills in artistic gymnastics for students. The educational process emerged from the specificity of the game and was sequential one after the other. The students interacted with their choice of exercises according to the educational model (Merril), and this helped increase the excitement in performing the lesson, and the exercises combined competition in performance with a spirit of joy and pleasure. By presenting the conclusions, the researchers recommend the following: The necessity of introducing the educational model (Merril) into the artistic gymnastics lesson for the purpose of developing the level of students and improving their skill performance for the third stage. Emphasizing the educational model (Merril) in teaching students in order to shorten time as well as economize on the tools used